Strategi Koping dengan harga Diri ODHA di Yayasan Medan Plus - Jek Amidos Pardede; Hafizuddin Hafizuddin; Asima Sirait (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
People living with HIV AIDS (PLWHA) not only experience problems physically or biologically, but also experience problems psychologically, socially and spiritually. The problem that often occurs in PLWHA is related to self-esteem. One way to increase the self-esteem of PLWHA is by implementing coping strategies. This study aims to determine the relationship between coping strategies and self-esteem of HIV / AIDS patients at the Medan Plus Foundation. The design of this study was a correlation analytic with a cross-sectional approach with a total population of 2152 and the sampling technique used the consecutive sampling method and identified 58 HIV / AIDS patients. Collecting research data using a questionnaire that has been tested for validity and reliability. The statistical test used was the chi-square test. The results of this study obtained coping strategies for PLWHA with the majority of emotion focused coping (62.1%) and the majority of PLHIV patients with low self-esteem (65.5%). The conclusion of this study is that there is a significant relationship between coping strategies and self-esteem of HIV / AIDS patients at Medan Plus Foundation.